2019
DOI: 10.1016/j.cgh.2019.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous Neoplasias Arise in a Higher Proportion of Colon Segments From Which Large Polyps Were Previously Removed, and Can be Used to Estimate Incomplete Resection of 10–20 mm Colorectal Polyps

Abstract: Incomplete resection of polyps could be an important cause of post-colonoscopy colorectal cancer. However, it is difficult to study progression of incompletely removed polyps or their clinical importance. We aimed to estimate incomplete polyp resection using risk of metachronous neoplasia per colon segment. METHODS:We performed a retrospective study of 1031 patients (6186 colon segments) who initially underwent resection of a large (10-20 mm) neoplastic polyp at 2 academic medical centers (from 2000 through 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Cancers thought to have arisen in sessile serrated lesions are also over-represented in interval cancer series, also suggesting that either missed or incompletely resected sessile serrated lesions may explain some post-colonoscopy CRCs (PCCRCs) 33. In a recent study that looked at neoplasia within the same colonic segments after resection of a 10–20 mm sized polyp, the estimated rate of incomplete resection for non-pedunculated polyps was higher (18.3%, 95% CI 14.2 to 22.5) than for pedunculated polyps (3.5%, 95% CI –0.7 to –11.3) 34. Thus, the GDG considered that a shift in ethos to more careful polypectomy, supported by selected site checks, may enable less frequent surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…Cancers thought to have arisen in sessile serrated lesions are also over-represented in interval cancer series, also suggesting that either missed or incompletely resected sessile serrated lesions may explain some post-colonoscopy CRCs (PCCRCs) 33. In a recent study that looked at neoplasia within the same colonic segments after resection of a 10–20 mm sized polyp, the estimated rate of incomplete resection for non-pedunculated polyps was higher (18.3%, 95% CI 14.2 to 22.5) than for pedunculated polyps (3.5%, 95% CI –0.7 to –11.3) 34. Thus, the GDG considered that a shift in ethos to more careful polypectomy, supported by selected site checks, may enable less frequent surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Studies have shown that 20% to 30% of interval CRC cases are attributable to incomplete resection of CRC precursors, with interval CRC cases often occurring at previous polypectomy sites or colon segments. [9][10][11][12][13][14] Although several recent studies have evaluated incomplete resection rates (IRRs) associated with different polypectomy techniques (eg, forceps or snare polypectomies), a systematic assessment of the reported IRRs across published studies is lacking. We were therefore interested in evaluating the IRR and factors influencing the IRR, such as use of hot vs cold snare, forceps, and/or submucosal injection, in a systematic review and meta-analysis.…”
mentioning
confidence: 99%
“…3 A recent retrospective study of 1031 patients who underwent resection of a large (10-20 mm) polyp showed, from findings on surveillance within 5 years, an estimated incomplete resection rate of 13.0%, indicating that initial incomplete resection leads to clinically relevant future pathology. 61 This rate was greater for nonpedunculated compared with pedunculated polyps (18.3% vs 3.5%; P < .001), and with piecemeal compared with en bloc resection (28.0% vs 9.2%; P < .001). It is certainly feasible that the inflammatory response provoked by incomplete polyp resection actually might accelerate neoplasia progression.…”
Section: Polyp-specific Polypectomy Techniquesmentioning
confidence: 87%